Improved Baited Remote Underwater Video (BRUV) for 24 h Real-Time Monitoring of Pelagic and Demersal Marine Species from the Epipelagic Zone - Prat-Varela, Alejandro; Torres, Agusti; Cervantes, Daniel; Aquino-Baleytó, Marc; Abril, Ana-Maria; Clua, Eric E. G. (Journal of marine science and engineering, 2023)
Bait-based remote underwater video (BRUV) systems are effective devices for remotely observing fish and other marine organisms in challenging environments. The development of a long duration (24 h) surface BRUV observation surveys allowed the monitoring of scarce and elusive pelagic sharks and the direct impact on non-targeted species of longline fishing in the Western Mediterranean. Technological limitations, such as the limited storage capacity and a single surface camera, were improved by (i) adding a deep camera equipped with light (below 80 m depth) and (ii) replacing Gopros with a multi-camera video surveillance system (surface and depth) with a storage capacity of several days and access to real-time observation. Based on a deployment effort of 1884 h video data, we identified 11 blue sharks (Prionace glauca) and one bluntnose sixgill shark (Hexanchus griseus), a deep-sea species that scarcely swims at the surface. The real-time observation capability was a powerful tool for reducing logistical costs and for raising environmental awareness in educational and outreach programmes.